End-User Assessment of the Graduate Performance From Islamic Bank Department, Faculty of Islamic Studies, Universitas Ahmad Dahlan: A Survey - Dwi Santosa Pambudi; Agus Susetyohadi; Nurul Heniirawati; Ajeng Putri Mahendra; Muhammad Fauzi Abdullah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
It is undeniable that external factors drive the development and growth of the Islamic bank industry in Indonesia. One of them is the supply of Islamic Human Resources (IHR) from various universities (PT), both private and public, that have opened Islamic banking study programs. However, the increasing availability of IHR from PT still needs to improve, including; link and math curriculum, absorption of graduates in the Islamic bank industry, competence, and performance of PT graduates. Therefore, this study aims to assess the performance of graduates of Islamic banking study programs who have worked in the Islamic banking and finance/islamic banking industry with an approach of technical competence, conceptual competence, and interpersonal ability. This type of research is descriptive quantitative. The sample is all alums of the Islamic banking study program who have worked in Islamic banks and finance/islamic for 2019-2021 with snowball sampling techniques. The sampling method uses questionnaires distributed to company leaders. The findings showed that most alums of Islamic banking study programs who work in the financial industry show high technical skills, conceptual abilities, and interpersonal skills.